Indigenous filmmaking practices: healing in times of climate crises - Ramirez-Loaiza, Viviana (Frontiers in Climate, 2023)
The psychological impacts of the climate crisis and its triggers can have long-lasting consequences for public mental health. Many indigenous communities have an in-depth understanding of these impacts, and some of their filmmakers have depicted them through their audiovisual work. By challenging colonial perspectives, these indigenous filmmakers offer invaluable insights into how communities might navigate into adaptation and recovery to cope with the challenges brought about by climate change. Unfortunately, audiovisual work has often been overlooked in climate-related disaster studies despite its significant contributions. Drawing on community-based feminism and the decolonial turn, I sought to explore the healing practices employed by communities in Upper Xingu, Brazil, through the practice of indigenous filmmaker Takuma Kuikuro. To achieve this, I drew on audiovisual analysis of Takumã Kuikuro’s documentaries and records (short videos) from the decolonial panorama. Additionally, I conducted semi-structured interviews with the filmmaker and three members of the People’s Palace Projects, who have worked closely with Takumã, culminating in a validation meeting. I highlight three key findings for this article: (i) healing through rituals as aesthetic and ethical-sacred practices with the territory; (ii) Bodies in collectivism, and (iii) cascading effects on healing audiences: weaving networks from reciprocities. In seeking a discussion of the findings, I contend that there is an inextricable bond between the community-based healing responses to the climate crisis shown by Takumã’s lenses and the Politics of the Bodies proposed by the Colombian philosopher Laura Quintana, allowing us to frame the decolonial understanding of healing as a political and collective action both within and with territories. Therefore, placing the Indigenous cinema as a source of knowledge will enable us to bring community-based discussions that disaster risk reduction has neglected due to its embeddedness in epistemic injustice, from which at-risk communities have been predominantly seen as incapable of knowing their geographies. The rituals and collaborative practices grounded in reciprocity demonstrate forms of adaptation in which mental health becomes a collective responsibility woven into nature at its core.